Haiti : poverty reduction strategy paper (IMF WashingtonUS, 2008)
Assesses poverty and inequality on the basis of the data gathered from the most recent surveys. Outlines the vision of state and non-state actors as well as the challenges to be met by 2015. Summarizes the major areas of work decided upon by the Government of Haiti at the July 25, 2006 International Conference. Deals with the macroeconomic framework and policies and covers the financing, implementation and monitoring of the Growth and Poverty Reduction Strategy.
Keywords: POVERTY ALLEVIATION